1995
DOI: 10.1074/jbc.270.52.31397
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction between the Escherichia coli RecF and RecR Proteins Dependent on ATP and Double-stranded DNA

Abstract: The DNA binding and ATPase activities of RecF protein are modulated by RecR protein. Stoichiometric amounts of RecF protein bind to double-stranded (ds) DNA (about 1 RecF monomer/4 -6 base pairs) in the presence of adenosine 5-O-(3-thio)triphosphate (ATP␥S), forming a homogeneous protein coating on the DNA. Little or no cooperativity is evident in the binding process. In the presence of ATP, RecF binding to dsDNA is much weaker, and no RecF protein coating forms. Instead, small numbers of RecF protomers are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
133
3
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(147 citation statements)
references
References 37 publications
6
133
3
5
Order By: Relevance
“…An 8-l sample of KaiC protein was diluted 100-fold with 200 mM ammonium acetate͞Hepes (10 mM, pH 7.0)͞10% glycerol, and adsorbed to the Alcianactivated carbon film for 3 min. After washing with the same buffer for 1 min, the sample was stained with 5% uranyl acetate followed by a very brief circular shadowing with platinum (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An 8-l sample of KaiC protein was diluted 100-fold with 200 mM ammonium acetate͞Hepes (10 mM, pH 7.0)͞10% glycerol, and adsorbed to the Alcianactivated carbon film for 3 min. After washing with the same buffer for 1 min, the sample was stained with 5% uranyl acetate followed by a very brief circular shadowing with platinum (19).…”
Section: Methodsmentioning
confidence: 99%
“…Reaction mixtures were prepared for EM by one of two procedures: (i) Alcian method (positive staining): Samples were prepared by adsorption to Alcian-activated carbon-coated grids as previously described (19). An 8-l sample of KaiC protein was diluted 100-fold with 200 mM ammonium acetate͞Hepes (10 mM, pH 7.0)͞10% glycerol, and adsorbed to the Alcianactivated carbon film for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, the RecR binding sites for the RecO and RecF have not been identified. In addition, E. coli RecR has been reported to form a dimer in solution (15,20), and its structural conformation has not been determined. Previously, we reported the backbone NMR assignments of Thermus thermophilus RecR (ttRecR) and suggested that it forms a symmetric homodimer in solution (23).…”
mentioning
confidence: 99%
“…recombinational DNA repair at replication forks (17,18). The RecF protein itself binds DNA and has a weak ATPase activity (19), both of which are enhanced by RecR binding (20,21). Furthermore, specific loading of the RecA protein onto the dsDNA-ssDNA junction is mediated by the RecF, RecO, and RecR proteins acting in concert, with no interaction between RecF and RecO detected (4).…”
mentioning
confidence: 99%
“…Reactions were stopped by adding ATP␥S to 1 mM and incubating at 37°C for 5 min. Reactions were spread by a modified adsorption procedure onto carbon films that were activated by either Alcian blue (33) or denatured BSA (as described above), with the following changes. The samples were diluted into 200 mM ammonium acetate, 10 mM HEPES, pH 8.0, and 10% (w/v) glycerol and were adsorbed to carbon films on an EM grid for 3 min.…”
mentioning
confidence: 99%